Selected microstructural and mechanical properties of open-cell metal foams - Depczyński, Wojciech (Strojniški vestnik, 2019)
The microstructure and mechanical properties of open-cell metal foams have long been studied from various angles. The materials discussed in this paper were fabricated using an unconventional sintering method and their properties are unique. An important part of the process is reduction of Fe(III) oxide, acting as a foaming agent and a space holder. Four powder mixtures were analysed: ASC100.29, ASC100.29 + C, DISTALOY SE and DISTALOY SE + C. The aim of the tests, performed with a specially developed setup, was to determine the impact energy absorption capacity of the Fe-based foams. From the results, it is clear that the metal foams can be used in many applications, including lightweight structures, filters, heat exchangers and energy-absorbing systems.
Keywords: disipacija energije; energy dissipation; Fe-based foams; kovinske pene z odprto poroznostjo; open-cell metal foams; pene na osnovi Fe; reduction of metal oxides; redukcija kovinskih oksidov; space holder technique; tehnika zasedanja prostora